PHYSICS AND SHEAR STRENGTH PARAMETER CORRELATION USING MODIFIED DIRECT SHEAR IN CRACKED SOIL - Rosa Irdiana; Indrasurya Budisatria Mochtar; Noor Endah Mochtar (Journal of Civil Engineering, 2021)
The theory of landslides due to cracks on the surface of the slope / cliff is known as the cracked soil theory. Several studies about shear parameters of cracked soil had been carried out. The latest research was about soil physical and shear strength parameters correlation in soft to stiff consistency soil. The soil conditions in that research were less representative of the slope / cliff soil consistency that can be very stiff. Therefore, further research for medium to very stiff consistency was conducted. Cracked test specimens were tested using water pressure variations and showed that water pressure had no significant effect. In cracked soils, the friction angle was not affected by the void ratio of the soil. Empirical formula for cracked soil at medium to very stiff consistency were for LL < 50%; Ø = 22˚ and LL ≥ 50%, Ø = -0.0024 LL2 + 0.2062 LL + 17.514.